Características do solo e da comunidade vegetal em área natural e antropizada de uma vereda na região de Uberlândia, MG - Guimarães, Antônio José Maia (2001)
Guimarães, Antônio José Maia. 2001. Characteristics of the soil and the plant community in natural and disturbed area of a vereda (palm swamp vegetation) near the city of Uberlândia, MG, Brazil. Msc. Thesis. UFU. Uberlândia, MG. 44p. The study aimed to compare natural and disturbed area of a vereda (palm swamp vegetation) according to its soil characteristics, depth of the water layer and the phytosociological structure of the plant community. The study was developed in a palm swamp situated in the south area of Uberlândia City, MG, inside the hydrographic basin of Tijuco River, at the geographic coordinates of 19° ir40.1”S and 48° 24’31.3”W. For the Chemical analysis it was collected soil in three different depths: 0-1 cm, 1-16 cm and 16-32 cm, and for humidity in the 0-10 cm layer. The phytosociological survey was perfomed with the linear method. Three classes of soil were recognized: Low-Humic Gley soil, Humic Gley soil and Organic soil, which had in average low pH rates and available bases. The highest percentage of organic matter and humidity occurred at the bottom of the palm swamp. In general, the highest contents of P, Ca and Mg occurred at the soil superficial layers. The depth of the water layer increased from the bottom to the edge of the palm swamp, following a declivity gradient. Significant differences occurred between the disturbed and preserved environments, at the intermediary zone of the vertent, in every analyzed season. At the vegetal community, 101 species were sampled, distributed in 70 genders and 29 families. The preserved vertent had lower richness of species than the disturbed area. Poaceae (33), Cyperaceae (13) and Asteraceae (10), were the families which had the highest number of species. Schizachyruim tenerum, Echnolaem inflexa and Louditia flanmiidci in the natural environment and Schizachyrium tenerum, Hypogynium virgatum and Ageratum fastigiatum in the disturbed, had higher relative frequency. The species with higher relative covering in the natural environment were Schizachyruim tenerum, Anthaenantiopsis trachystachya and Echnolaena inflexa, and in the disturbed, Schizachyrium tenerum, Hypogynium virgatum and Hyparrhenia bracteata. Significant differences were detected between natural and disturbed environment at the relative covering and average vegetation height.